Improving Civics Learning Outcomes Through Numbered Heads Together Class II Elementary School Learning Model - Ariska Yanuar Sari (Social, Humanities, and Educational Studies (SHES): Conference Series, 2020)
The purpose of this research was to improve learning outcomes of Pancasila and Citizenship Education through the Numbered Head Together (NHT) model for Class II students of SDIT Nur Rohman. The research method is classroom action research with two cycles. The data analysis technique used is descriptive quantitative data analysis. Based on the improvement of the learning cycle I and cycle II, the learning outcomes of the first cycle can be presented which can achieve completeness as many as 20 students (80.00%) with a class average of 81,2. Cycle II learning outcomes that can achieve completeness are 25 students (100%) with a class average of 86,9. Judging from the percentage of completeness and the average value of increasing learning outcomes, it can be concluded that the use of NHT type cooperative model in II class  SDIT Nur Rohman Slogohimo can significantly improve learning outcomes